Determinants of corporate cash holdings in public listed firms in Malaysia - Hanan, Alam Faizli (2017)
This study examines the determinants of corporate cash holdings of 265 public listed firms in Malaysia from 2006 to 2015. All sectors are included in this sample, except the financial and utility sectors due to their different business reporting nature. The motive of cash holdings is explained based on the transaction, precautionary, agency, and speculative motives. Corporate cash holdings is measured by cash and cash equivalents by the total asset, while the determinant variables are size, leverage, profitability, dividend, growth opportunity, net working capital, and capital expenditure. The data were collected from Thomson Reuters Datastream database and Bursa Malaysia website. The data were then analysed using Linear Regression through the IBM SPSS Software. This study found that the corporate cash holdings in Malaysian public listed firms are determined by leverage, profitability, growth opportunity, net working capital, and capital expenditure, while firm size and dividend payout do not influence the corporate cash holdings. The result also shows that leverage, net working capital, and capital expenditure negatively influence corporate cash holdings, while profitability and growth opportunity positively influence corporate cash holdings. This implies that companies with higher leverage, liquidity, and capital expenditure will hold lower cash, while more profitable firms and firms with higher growth rate will hold more cash and vice versa. This study contributes to the existing literature on the factors that determine the corporate cash holdings.